(untitled) (Indian Journal of Arid Horticulture, 2013)
The present study was carried out at Panchmahals district of middle Gujarat during 2011-12. Okra is one of the most important vegetable crop of the country and India is the largest producer in the World. The development of the Agriculture is primarily depends on the application of the scientific technologies by making the best use of available resources. One of the major constraints of traditional okra farming is low productivity because of non-adoption of advanced technologies. To increase the production, productivity and quality of agricultural produce, Front Line Demonstrations is conducting at various farmers’ field. All the recommended practices were provided to the selected farmers. The data related to cost of cultivation, production, productivity, gross return and net return were collected as per schedule and analyzed. Results of the present study revealed that the improved variety of Okra Gujarat Okra-2 recorded the higher yield (105.90 q/ ha) as compared to local check (87.60 q/ ha) traditionally grown by the farmers. The percentage increase in the yield over local check 20.89 was recorded. The technology gap in terms of productivity (9.1 q/ha) were computed. The technology index values 7.91 % was recorded. The results of study indicated the gap existed in the potential yield and demonstration yield is due to soil fertility and weather conditions. By conducting Front Line Demonstrations (FLDs) of proven technologies, yield potential of Okra can be increased upto great extent. This will substantially increase the income as well as the livelihood of the farming community